New harvester for tubers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A hand-operated device for pulling cassava tubers out of the ground has been designed and manufactured by the Agricultural Mechanization Development Programme (AMDP) of the National Institute in the Philippines. The device weighs 2.5 kilos (5...